Cystatin C, renal resistance index, and kidney injury molecule-1 are potential early predictors of diabetic kidney disease in children with type 1 diabetes - Trutin, Ivana; Bajic, Zarko; Turudic, Daniel; Cvitkovic-Roic, Andrea; Milosevic, Danko (Frontiers in Pediatrics, 2022)
Background Diabetic kidney disease (DKD) is the main cause of end-stage renal disease in patients with diabetes mellitus type I (DM-T1). Microalbuminuria and estimated glomerular filtration rate (eGFR) are standard predictors of DKD. However, these predictors have serious weaknesses. Our study aimed to analyze cystatin C, renal resistance index, and urinary kidney injury molecule-1 (KIM-1) as predictors of DKD. Methods We conducted a cross-sectional study in 2019 on a consecutive sample of children and adolescents (10–18 years) diagnosed with DM-T1. The outcome was a risk for DKD estimated using standard predictors: age, urinary albumin, eGFR, serum creatinine, DM-T1 duration, HbA1c, blood pressure, and body mass index (BMI). We conducted the analysis using structural equation modeling. Results We enrolled 75 children, 36 girls and 39 boys with the median interquartile range (IQR) age of 14 (11–16) years and a median (IQR) duration of DM-T1 of 6 (4–9) years. The three focal predictors (cystatin C, resistance index, and urinary KIM-1) were significantly associated with the estimated risk for DKD. Raw path coefficients for cystatin C were 3.16 [95% CI 0.78; 5.53; p = 0.009, false discovery rate (FDR) < 5%], for renal resistance index were –8.14 (95% CI –15.36; –0.92; p = 0.027; FDR < 5%), and for urinary KIM-1 were 0.47 (95% CI 0.02; 0.93; p = 0.040; FDR < 5%). Conclusion Cystatin C, renal resistance index, and KIM-1 may be associated with the risk for DKD in children and adolescents diagnosed with DM-T1. We encourage further prospective cohort studies to test our results.